Contemporary complex systems and their dependability : proceedings of the Thirteenth International Conference on Dependability and Complex Systems DepCoS-RELCOMEX, July 2-6, 2018, Brunów, Poland /: proceedings of the Thirteenth International Conference on Dependability and Complex Systems DepCoS-RELCOMEX, July 2-6, 2018, Brunów, Poland. (2018) - Unknown
No abstract available